C‐MYC and p53 expression highlight starry‐sky pattern as a favourable prognostic feature in R‐CHOP‐treated diffuse large B‐cell lymphoma. (9th August 2021) - Bouroumeau, Antonin; Bussot, Lucile; Bonnefoix, Thierry; Fournier, Cyril; Chapusot, Caroline; Casasnovas, Olivier; Martin, Laurent; McLeer, Anne; Col, Edwige; David‐Boudet, Laurence; Lefebvre, Christine; Algrin, Caroline; et al.
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is a clinically heterogeneous entity, in which the first‐line treatment currently consists of an immuno‐chemotherapy regimen (R‐CHOP). However, around 30% of patients will not respond or will relapse. Overexpression of c‐MYC or p53 is frequently found in DLBCL, but an association with prognosis remains controversial, as for other biomarkers previously linked with DLBCL aggressivity (CD5, CD23, or BCL2). The aim of this study was to explore the expression of these biomarkers and their correlation with outcome, clinical, or pathological features in a DLBCL cohort. Immunohistochemical (c‐MYC, p53, BCL2, CD5, and CD23), morphological ('starry‐sky' pattern [SSP]), targeted gene panel sequencing by next‐generation sequencing (NGS), and fluorescence in situ hybridisation analyses were performed on tissue microarray blocks for a retrospective cohort of 94 R‐CHOP‐treated de novo DLBCL. In univariate analyses, p53 overexpression (p53 high ) was associated with unfavourable outcome ( p  = 0.04) and with c‐MYC overexpression ( p  = 0.01), whereas c‐MYC overexpression was linked with an SSP ( p  = 0.004), but only tended towards an inferior prognosis ( p  = 0.06). Presence of a starry‐sky morphology was found to be correlated with better survival in p53 high DLBCL ( p  = 0.03) and/or c‐MYC‐positive DLBCL ( p  = 0.002). Furthermore, NGS data revealed that these three variables were associated with somatic mutations ( PIM1, TNFRSF14, FOXO1, and B2M ) involved in B‐cell proliferation, survival, metabolism, and immune signalling. Taken together, these results show that the SSP pattern seems to be a protective factor in high‐risk DLBCL subgroups and highlight cell death as a built‐in failsafe mechanism to control tumour growth.